Hubungan Kekuatan Otot Perut terhadap Kemampuan Passing Futsal pada Mahasiswa PJKR Universitas Negeri Gorontalo - Joni Taufik Hidayat (Departement of Mathematics Education, 2023)
The purpose of this study was (1) to determine the relationship between abdominal muscle strength and passing ability in PJKR UNG futsal players. This research is a correlation study. The population in this study consisted of 12 PJKR UNG futsal players. The sampling technique used was total sampling, so the sample size in this study was 12 people. The test instruments used were the sit-up test and the passing-stopping test. The data analysis technique used was the r-test. Based on the results, it was found that (1) There is a relationship between abdominal muscle strength and passing ability in PJKR UNG futsal players with an r-value of 0.526 and a coefficient of determination of 27.30%.